Transformative Approaches to Sustainable Development at Universities : Working Across Disciplines - Leal Filho, Walter (World Sustainability Series,, 2015)
This book documents and disseminates experiences from a wide range of universities, across the five continents, which showcase how the principles of sustainable development may be incorporated as part of university programmes, and present transformatory projects and programmes, showing how sustainability can be implemented across disciplines. Sustainability in a higher education context is a fast growing field. Thousands of universities across the world have signed declarations or have committed themselves to integrate the principles of sustainable development in their activities: teaching, research and extension, and many more will follow.  .